Manejo de enfermedades foliares aplicando fungicidas de protección y sistémicos solo o mezclados en el cultivo de tomate (lycopersicon esculentum) en Lamas - Perú - Reategui Vasquez, Edinson (2001)
This research was conducted in the field Horticultural Jorge Pelaez Ing in Fencing Munich district, district and province of Lamas, San Martin region, Peru.; at South latitude 06 ° 20'15 "West Longitude 76 ° 30 '5" and 920 m altitude. s. n. m. m .; e! to determine the toxic effect and efficiency of protectant and systemic fungicides formulated alone or in mixtures for handling pathogenic fungi that cause leaf diseases in tomato variety Rio Grande and make economic analysis of tomato production with each Treatments. Before applying fungicides samples of the tomato leaf is transported, the Plant Health Laboratory of the University, for analysis and taxonomic keys using the following pathogens were identified. Stemphytlium sp, Pftytophthora sp. and Botrytis sp. Fungicides were applied to tomato plants after 10 days transplanted to the field, under the Complete Block design) with 11 treatments at Azar, 10 treatments of fungicides (fosetyl Al + Mancozeb + Cymoxanil, at doses of 2.5 to 3 , 75 per thousand; Fentin acetate + Mancozeb, in doses from 1.5 to 2.5 per thousand; Cymoxanil + Mancozeb, in doses from 2.5 to 3.75 per thousand, Mancozeb, at doses of 1.5 to 2 , 5 per thousand; Metalaxyl + Mancozeb, at doses of 2.5 to 3.75 per thousand and a control (no fungicide) with 4 repetitions the fungicide, Fosetyi Al + Mancozeb + Cymoxanil dose of 2.5 to 3. , 5 per thousand, reduced to 0% to staining Phytophthora sp. and Botrytis sp. to 1.99%, while it fungicide Mancozeb + Metaiaxil dose 2.5 to 3.75 mil, better controlled Stemphylium sp., reducing it to 17.31% 16.71. in accordance with yields of 84 963.60 and 83 249.33 Kg. / ha, and the cost-benefit analysis of 12.09 and 12.43% representing the cost profit, was better, the application of the fungicide fosetyl Al + Mancozeb + Cymoxanil dose of 2.5 to 3.5 per thousand.